Constructing an Artificial Intelligence Ethics Framework Based on Maqasid Shariah for Sustainable Digital Transformation Governance - Hasmia Wahyunisa; Aminullah (Institut Bahri Asyiq Galis Bangkalan, 2025)
The rapid development of artificial intelligence across multiple sectors has generated complex ethical challenges that require a contextual normative framework. The ongoing expansion of digital transformation has necessitated the integration of technological innovation with principles of social sustainability. This study aimed to construct an ethical framework for artificial intelligence based on the principles of Maqasid Shariah to support sustainable digital transformation. The research employed a descriptive qualitative approach using a systematic literature review of reputable scholarly articles published between 2016 and 2025, selected through a structured screening protocol. Data were analyzed through content analysis and thematic analysis to synthesize findings across studies. The results indicated that the five dimensions of Maqasid Shariah, namely the protection of life, intellect, property, lineage, and religion, demonstrated operational relevance in the development of transparent, accountable, and public-oriented artificial intelligence governance. The proposed framework integrated normative principles and technological governance into a coherent conceptual structure. This study contributed theoretically to the advancement of value-based technology ethics and provided practical guidance for the formulation of sustainable artificial intelligence policies.